Síntese em fase sólida, caracterização e estudo conformacional da δ melantropina e da δ melantropina oxidada - Alles, Irene Maria (2005)
The δ melanotropin is a peptide with sequence H-Ser-Met-Glu-Val-Arg-Gli-Trp-OH. The synthesis of this peptide was carried out by the methodology in solid phase, being the sequence synthesized on a polymeric support by means of the successive incorporation of each amino acid. After the desired sequence was synthesized, we proceeded with its cleavage from the solid support by means of acidolysis with cocktail R (TFA-thioanisole-EDT-anisol). The employed support was p-methylbenzhydrylamine resin (MBHA) and the handle (linker) used was the 3-(4 -hydroxymethylphenoxy)propionic acid. The coupling reactions were carried out using diisopropylcarbodiimine (DIC) in presence of 1-hydroxybenzotriazole (HOBt). During the procedures of purification of the δ melanotropin, its partial oxidation was observed, getting up to 35% of H-Ser-Met(O)-Glu-Val-Arg-Gli-Trp-OH. In this work it was achieved a conformational analysis of the synthetic δ melanotropin using circular dicroism spectroscopy. There were also studied some parameters as concentration of trifluretanol, temperature and concentration of the peptide. It was observed that the preferential conformation of the peptide is random coil.